Guidelines for treatment of autoimmune neuromuscular transmission disorders. - Skeie, G; Apostolski, S; Evoli, A; Gilhus, N; Illa, I; Harms, L; Hilton-Jones, D; Melms, A; Verschuuren, J; Horge, H (2010)
BACKGROUND: Important progress has been made in our understanding of the autoimmune neuromuscular transmission (NMT) disorders; myasthenia gravis (MG), Lambert-Eaton myasthenic syndrome (LEMS) and neuromyotonia (Isaacs' syndrome). METHODS: To prepare consensus guidelines for the treatment of the autoimmune NMT disorders, references retrieved from MEDLINE, EMBASE and the Cochrane Library were considered and statements prepared and agreed on by disease experts. CONCLUSIONS: Anticholinesterase drugs should be given first in the management of MG, but with some caution in patients with MuSK antibodies (good practice point). Plasma exchange is recommended in severe cases to induce remission and in preparation for surgery (recommendation level B). IvIg and plasma exchange are effective for the treatment of MG exacerbations (recommendation level A). For patients with non-thymomatous MG, thymectomy is recommended as an option to increase the probability of remission or improvement (recommendation level B). Once thymoma is diagnosed, thymectomy is indicated irrespective of MG severity (recommendation level A). Oral corticosteroids are first choice drugs when immunosuppressive drugs are necessary (good practice point). When long-term immunosuppression is necessary, azathioprine is recommended to allow tapering the steroids to the lowest possible dose whilst maintaining azathioprine (recommendation level A). 3,4-Diaminopyridine is recommended as symptomatic treatment and IvIG has a positive short-term effect in LEMS (good practice point). Neuromyotonia patients should be treated with an antiepileptic drug that reduces peripheral nerve hyperexcitability (good practice point). For paraneoplastic LEMS and neuromyotonia optimal treatment of the underlying tumour is essential (good practice point). Immunosuppressive treatment of LEMS and neuromyotonia should be similar to MG (good practice point).